Infrastructure's Role in Sustaining Asia's Growth - Douglas H. Brooks; Eugenia C. Go (Asian Development Bank (ADB), 2011)
This paper provides a comprehensive overview of the issues, policies, and political economy of infrastructure investment, and a review of empirical literature of the relationship between growth and infrastructure. Empirical estimations using the growth accounting framework for a panel of 123 economies confirm that while infrastructure contributes to growth, the extent of the contribution generally varies according to the level of income of countries. Telecommunications are most important for low-income countries, while transportation and energy are the most relevant for middle-income and high-income economies, respectively. Results pertaining to the Asia and Pacific region reveal infrastructure on telecommunications, roads, and energy generation to have been supportive of growth in the region.
hdl:11540/1986
Keywords: 330; Infrastrukturinvestition; Wirkungsanalyse; Wirtschaftswachstum; Vergleich; Asien